Impact of the integration of lupine (Lupinus albus) into crop rotation on the extent of soil compaction in the Westsik longterm field trial - Zsombik, László; Tótok, Veronika (Acta Agraria Debreceniensis, 2018)
In order to reduce or eliminate soil compaction, rational crop rotation and appropriate sequence of crops have an increasingly important role in addition to mechanical and tillage solutions. In this respect, introduction of greening in recent years has been a major step, which focuses on aspects of environmentally conscious, soil conserving farming and the improvement of biodiversity. The cornerstone of this strategy is the cultivation of crops that have a beneficial effect on soil properties, such as the use of nitrogen-fixing plants and green manure plants in the cultivation system that have a beneficial effect on soil structure. In our examinations, penetrometer measurements were carried out in the second longest crop rotation-based field experiment in Europe in order to quantify the effects of green crops and crop rotation strategies on soil resistance. Our aim was to evaluate and compare the impact of lupine (Lupinus albus) on the penetration resistance of soil on sour sandy soils. At the time of the penetration resistance measurement, different crop rotations had a significant effect on the development of the parameter in the examined soil layer. The most favourable penetration resistance values were found in the crop rotation, which included lupine as a green manure. The favourable effect is dominant below the cultivated layer (0–40 cm), which is statistically verified. The values of penetration resistance of the cultivated soil layer of lupine sown as primary green manure did not differ significantly from the values measured in the case of the fallowing-based crop rotation. Therefore, the use of lupine green manure instead of fallowing could be worth considering by practical application due to its favourable effects on soil penetration resistance. The use of lupine green manure after the production of rye cultivation resulted in penetration parameters similar to fallowing, irrespective of the green crop and the applied amount of nitrogen fertilizer, which justifies the cultivation of the crop as green manure. In the case of potato cultivating, recorded compaction within the cultivated layer is an obvious consequence of mechanical compaction during harvest; therefore, machinery operations are decisive for the development of penetration resistance values of the cultivated layer. In addition to the beneficial effect of lupine as a green manure crop on soil condition, its nitrogen-fixing ability is also important; it stresses the utilisation of the crop of sour sandy soils for the sake of proper soil management.